Implementation Of Card Sort Active Learning Strategies To Increase Mathematics Learning Outcomes For Ii Class Students Of SD Negeri 013 Kepenuhan Tp 2017/2018 - Hasmah Hasmah (STKIP Rokania Pasir Pangaraian, 2021)
, This research is a classroom action research activity based on the low mathematics learning outcomes of students. The formulation of the problem in this study is how the implementation of the Card Sort strategy can further improve the mathematics learning outcomes of second grade students of SD Negeri 013 Kepenuhan. The motivation of this research is to describe the use of Card Sort strategy to further improve mathematics learning outcomes for second grade students of SD Negeri 013 Kepenuhan. The subjects of the research were the second grade students of SDN 013 Kepenuhan, totaling 20 people. The object of this research is the application of the card sort type of active learning strategy and mathematics learning outcomes. This research was conducted in two cycles. Data collection techniques used are test, observation, and documentation methods. The strategy of investigating information in this examination is graphic examination. The conclusion of the research is that the application of the card sort type of active learning strategy can improve the mathematics learning outcomes of second grade students of State Elementary School 013 Kepenuhan, especially on the subject of dividing two-digit numbers